Parental knowledge, attitudes, and practices regarding the use of prescribed inhalers in asthmatic children attending Ambulatory Healthcare Services Clinics - Al-Ali, Lateefa; Al Jasmi, Shaima; Al Yammahi, Laila; Syeed, Adnan; Darwish, Ebtihal (Ibnosina Journal of Medicine and Biomedical Sciences, 2019)
Background: Bronchial asthma affects 10%–15% of children worldwide. Parental attitudes constitute a major factor in helping to achieve successful asthma control in children. We aimed to assess parental knowledge, attitudes, and practices (KAPs) regarding the use of prescribed inhalers for children with asthma in Abu Dhabi, United Arab Emirates. Subjects and Methods: This was a cross-sectional survey-based study conducted at the Ambulatory Healthcare Services (AHS) clinics across Abu Dhabi. Questionnaires that assessed parental KAPs regarding inhalers used in asthma were distributed to 365 parents of children (≤10 years of age) who had a diagnosis of asthma and had been followed up at an Abu Dhabi AHS clinic in the past 12 months. Results: Only 9.3% of the participants correctly answered ≥75% of the questions assessing knowledge, whereas 49.0% gave positive responses to ≥80% of the questions related to attitudes and 56.2% correctly performed ≥53% of the practices. Higher levels of knowledge and practices were demonstrated among nonnationals and those with a higher level of education, and more positive attitudes were found among older parents. Knowledge and attitudes positively correlated with the level of practice. Conclusions: Although a minority of the participants had a good level of knowledge, they tended to demonstrate positive attitudes and good practices with regard to the use of an inhaler. Overall, a much more concerted effort is required by healthcare providers in Abu Dhabi to assess parental understanding about their child's inhaler as well as educate parents about their practical use.
Keywords: Abu Dhabi; Ambulatory Healthcare Services; asthma; attitudes; knowledge; parents; practices